A revised model of TRAIL‐R2 DISC assembly explains how FLIP(L) can inhibit or promote apoptosis. (3rd February 2020) - Humphreys, Luke M; Fox, Jennifer P; Higgins, Catherine A; Majkut, Joanna; Sessler, Tamas; McLaughlin, Kirsty; McCann, Christopher; Roberts, Jamie Z; Crawford, Nyree T; McDade, Simon S; Scott, Christopher J; Harrison, Timothy; et al.
Abstract: The long FLIP splice form FLIP(L) can act as both an inhibitor and promoter of caspase‐8 at death‐inducing signalling complexes (DISCs) formed by death receptors such as TRAIL‐R2 and related intracellular complexes such as the ripoptosome. Herein, we describe a revised DISC assembly model that explains how FLIP(L) can have these opposite effects by defining the stoichiometry (with respect to caspase‐8) at which it converts from being anti‐ to pro‐apoptotic at the DISC. We also show that in the complete absence of FLIP(L), procaspase‐8 activation at the TRAIL‐R2 DISC has significantly slower kinetics, although ultimately the extent of apoptosis is significantly greater. This revised model of DISC assembly also explains why FLIP's recruitment to the TRAIL‐R2 DISC is impaired in the absence of caspase‐8 despite showing that it can interact with the DISC adaptor protein FADD and why the short FLIP splice form FLIP(S) is the more potent inhibitor of DISC‐mediated apoptosis. Synopsis: A revised model of TRAIL‐R2 DISC assembly and stoichiometry can explain the ability of FLIP(L) to act as either an inhibitor or activator of apoptosis signalling in these complexes. The stoichiometry of the pseudo‐caspase FLIP(L) relative to caspase‐8 at the TRAIL‐R2 death‐inducing signalling complex (DISC) was re‐examined. When equistochiometric with capase‐8, FLIP(L) inhibits apoptosis at the TRAIL‐R2 DISC (caspase‐8:FLIP(L) ratio ≈ 1:1). Sub‐stoichiometric FLIP(L) (caspase‐8:FLIP(L) ratio > 1:1) accelerates caspase‐8 activation. The revised model of DISC assembly predicts that relatively small changes in FLIP(L)'s DISC recruitment can have profound effects on cell death signalling. Abstract : A revised model of TRAIL‐R2 DISC assembly and stoichiometry can explain the ability of FLIP(L) to act as either an inhibitor or activator of apoptosis signalling in these complexes.